Implementasi Model Timmons dalam pembinaan startup berbasis teknologi pada inkubator bisnis - Cut Irna Setiawati; Putri Meuthia Pratiwi (Jurnal Manajemen Maranatha, 2019)
In 2013 Indonesia has developed Science Techno Park one of them Bandung Techno Park with business incubator Startup Corner. Startup Corner program has stages of joining starting from Registration, Selection through Presentation Startup Then Pre Incubation, Pre Pre-incubation destination to know the area of ??Bandung Techno Park area. Last is implementing Incubation. However, Startup Corner has not been maximized in identifying aspects of opportunities, teams and resources. The purpose of this research is to know the role of Startup Corner in developing startup which has been aspect of opportunity, team, and resources. In this research use descriptive qualitative method, with approach of Timmons Model. The results of the role of Startup Corner in developing startup from aspect of opportunity, team, resource. The role of Startup Corner in developing startup from aspect of opportunity, based on the dimension of idea has played a role in product development and business model, selling price, and then second dimension that is market demand of Startup Corner role that is directing in translating customer so that can assist in reaching customer opportunity and expanding market reach . Furthermore the role of Startup Corner in developing startup of team aspect based on leader dimension and team quality. The Corner Startup has played a role in the leader's dimension through training to shape the entrepreneurial character during Pre Incubation activities. In creating the quality of the team submitted by startup who join but the work culture is advisable to work discipline in accordance with the BTP working hours other than that Startup Corner helps in disseminating recruitment information for startup requiring members. The role of Startup Corner in developing startup from the aspect of resources. Startup Corner has provided physical facilities, then assistance to make the legality of a business entity, patent but there is no funding for the sustainability of a startup, then diverted in incubation or other programs.